Pharmacological and cardiovascular perspectives on the treatment of COVID-19 with chloroquine derivatives - Zhang Xiao-lei; Li Zhuo-ming; Ye Jian-tao; Lu Jing; Ye Lingyu Linda; Zhang Chun-xiang; Liu Pei-qing; Duan Dayue D (Acta Pharmacologica Sinica, 2020)
The novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19) and an ongoing severe pandemic. Curative drugs specific for COVID-19 are currently lacking. Chloroquine phosphate and its derivative hydroxychloroquine, which have been used in the treatment and prevention of malaria and autoimmune diseases for decades, were found to inhibit SARS-CoV-2 infection with high potency in vitro and have shown clinical and virologic benefits in COVID-19 patients. Therefore, chloroquine phosphate was first used in the treatment of COVID-19 in China. Later, under a limited emergency- use authorization from the FDA, hydroxychloroquine in combination with azithromycin was used to treat COVID-19 patients in the USA, although the mechanisms of the anti-COVID-19 effects remain unclear. Preliminary outcomes from clinical trials in several countries have generated controversial results. The desperation to control the pandemic overrode the concerns regarding the serious adverse effects of chloroquine derivatives and combination drugs, including lethal arrhythmias and cardiomyopathy. The risks of these treatments have become more complex as a result of findings that COVID-19 is actually a multisystem disease. While respiratory symptoms are the major clinical manifestations, cardiovascular abnormalities, including arrhythmias, myocarditis, heart failure, and ischemic stroke, have been reported in a significant number of COVID-19 patients. Patients with preexisting cardiovascular conditions (hypertension, arrhythmias, etc.) are at increased risk of severe COVID-19 and death. From pharmacological and cardiovascular perspectives, therefore, the treatment of COVID-19 with chloroquine and its derivatives should be systematically evaluated, and patients should be routinely monitored for cardiovascular conditions to prevent lethal adverse events.